Absence of Crimean-Congo haemorrhagic fever virus in the tick Hyalomma aegyptium parasitizing the spur-thighed tortoise (Testudo graeca) in Tunisia - Fares, Wasfi (Parasite, 2019)
Free-ranging spur-thighed tortoises Testudo graeca, captured in different habitat types of Northern Tunisia from March to April 2017, were examined for tick infestation: 134/147 (91%) were infested. The overall infestation intensity and abundance was 8.5 and 7.8, respectively. From these tortoises, 1174 ticks were collected, of which 10% (n = 120) taken from 18 randomly-selected tortoises were identified at the species level; the remaining ticks were examined for the presence of Crimean-Congo haemorrhagic fever virus (CCHFv) by real time RT-PCR. Only adult Hyalomma aegyptium were found, suggesting a high degree of host specificity to tortoises. No CCHFv was detected in ticks. Considering the absence of CCHFv in Hyalomma aegyptium infesting its main host, the spur-thighed tortoise, this tick species is unlikely to play a major role in the epidemiology of CCHF. Therefore, more studies are needed to investigate the circulation of this arbovirus between livestock and other tick species from North Africa.